Capacity Evolution of Flexible Units Based on a Dual-Timescale Dynamic Model under Dual Carbon Goals - LI Kecun, HUANG Zhenyu, YOU Xingxing, QIU Gao, LIU Youbo, LIU Junyong (Dianli jianshe)
In the context of “carbon peaking” and “carbon neutrality，” the generation method for power systems is gradually transitioning from traditional generation to renewable energy source generation， posing challenges to the stability of the power supply in the grid. The significance of flexible generator units has become increasingly evident. Concurrently， ongoing reforms in the electricity market are yet to clearly define the self-profit development trends of flexible units. Traditional development models often lack the accurate elements of the electricity price generation process. This paper proposes a dual-timescale dynamic model that combines system dynamics with spot market clearing to simulate the self-profit growth trends of flexible gas units and energy storage systems under more realistic electricity price scenarios. First， the quantitative and feedback relationships among market elements are analyzed， and a system dynamics model is established to simulate the investment and development of various power generation types. Second， a spot market-clearing model based on unit commitment optimization is presented to validate the system's operational constraints and calculate spot market-clearing results. A dual-timescale dynamic model is introduced that integrates the spot market-clearing model as a core component of the system dynamics model. Finally， different subsidy schemes for flexible units are discussed， and recommendations for power system planners and relevant policymakers are provided based on the simulation results.